Fat distribution pattern as a risk factor for chronic disease among the tribals of Northeast India - Tungdim, Mary Grace (Array, 2009)
Abstract: The objective of this study was to investigate the effect of pulmonary tuberculosis on the body fat distribution pattern and the sensitivity of different skinfold sites with disease and treatment among the adult tribals of Manipur, Northeast India. A total of four anthropometric measurements and skinfold thickness at five different sites were taken for the study. The indices of adiposity like body mass index, waist hip ratio and grand mean thickness were computed. The cross sectional sample included tuberculosis (TB) patients (n=167) at different stages of treatment and healthy non patients as controls (n=80). The subjects ranged in age from 20–40 years. Wasting of muscle mass and decrease in fat mass because of chronic disease (TB) and overall improvement in these components along with redistribution of fat with TB treatment was observed